Piano sonata no. 24 in F-sharp major, op. 78, edited by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Editor:::::::::::: (Stuttgart; Germany; Eduard Hallberger, 2024)
Mid-nineteenth century edition of the Piano Sonata no. 24 in F-sharp major, op. 78, edited by Ignaz Moscheles and published by Eduard Hallberger in Stuttgart as no. 24 of the series "L. v. Beethoven's sämmtliche Sonaten für Pianoforte."